Identification of miR-26 as a key mediator of estrogen stimulated cell proliferation by targeting CHD1, GREB1 and KPNA2 - Tan, Sheng; Ding, Keshuo; Li, Rui; Zhang, Weijie; Li, Gaopeng; Kong, Xiangjun; Qian, Pengxu; Lobie, Peter E; Zhu, Tao (Breast cancer research : BCR, 2014)
Estrogen signaling is pivotal in the progression of estrogen receptor positive breast cancer primarily by the regulation of cell survival and proliferation. Micro (mi)RNAs have been demonstrated to be regulated by estrogen to mediate estrogenic effects. Herein, we determined the role of estrogen regulated miR-26 and its underlying molecular mechanisms associated with estrogen receptor (ER)+ breast cancer proliferation. The expression of miR-26a and miR-26b was evaluated by real-time quantitative (RT)-PCR. The expression of miR-26a or miR-26b was modulated in ER+ breast cancer cells (MCF-7 and T47D) and tumor cell growth in vitro and an in vivo xenograft model was determined. Bioinformatics analyses were utilized to screen for estrogen responsive genes, which were also predicted to be targeted by miR-26. Luciferase reporter assays were performed to confirm miR-26 regulation of the 3' UTR of target genes. The levels of miR-26 target genes (CHD1, GREB1 and KPNA2) were evaluated by western blotting and immunohistochemistry. Estrogen reduced the expression of miR-26a and miR-26b in ER+ breast cancer cells. Forced expression of miR-26a or miR-26b significantly inhibited the estrogen stimulated growth of ER+ breast cancer cells and tumor growth in xenograft models, whereas miR-26a/b depletion increased the growth of ER+ breast cancer cells in the absence of estrogen treatment. Screening of estrogen responsive genes, which were also predicted to be targeted by miR-26, identified GREB1 and nine other genes (AGPAT5, AMMECR1, CHD1, ERLIN1, HSPA8, KPNA2, MREG, NARG1, and PLOD2). Further verification has identified nine genes (AGPAT5, CHD1, ERLIN1, GREB1, HSPA8, KPNA2, MREG, NARG1 and PLOD2) which were directly targeted by miR-26 via their 3' UTR. Functional screening suggested only three estrogen regulated miR-26 target genes (CHD1, GREB1 and KPNA2) were involved in the regulation of estrogen promoted cell proliferation. Depletion of either CHD1, GREB1 or KPNA2 significantly abrogated the enhanced growth of ER+ breast cancer cells due to miR-26 depletion. We further demonstrated that estrogen stimulated c-MYC expression was both sufficient and necessary for the diminished expression of miR-26a and miR-26b. We have identified a novel estrogen/MYC/miR-26 axis that mediates estrogen stimulated cell growth via CHD1, GREB1 and KPNA2.